1090 Relationship Between Neurotrophins and Brain Structure in Preterm Growth Restricted Babies. (October 2012) - Parkes, L; Atkinson, J; Miyan, J; Hendrickson, A; Victor, S
Abstract : Background: Neurotrophins are responsible for the growth and survival of neurons during early brain development. Intrauterine growth restriction (IUGR) leads to alterations in brain structure. Aim: To explore the relationship between neurotrophins and brain structure in preterm IUGR babies. Methods: 31 babies born between 28 and 36 weeks' gestation were studied. 19 babies were IUGR with individualised birth weight (normalised for sex, ethnicity, parity, maternal BMI) below 3 rd centile. 12 babies were appropriately grown with individualised birth weight between the 25 th and 75 th centile. Blood neurotrophin concentrations were measured using protein chip technology in 30 babies (19 IUGR and 11 controls) between 2 and 7 days after birth. In 14 babies (7 from each group) MRI brain was performed at term equivalence. Results: Fractional anisotropy (FA) was lower in IUGR babies compared to controls in 7 out of 8 regions with no statistical significance. Apparent diffusion coefficient (ADC) was lower in IUGR babies compared to controls in 6 out of 8 regions, reaching significance in frontal lobes. 7 out of 8 regions were smaller in IUGR babies compared to the control babies, reaching significance in the dorso-medial pre-frontal cortex. Differences did not persist when normalised for intracranial volume. Serum neurotrophin concentrations were elevated in IUGR babies but did not reach statistical significance. Using multiple regression only FA of right frontal lobe was significantly related to BDNF (R= 0.65; p=0.012). Conclusion: IUGR babies showed no differences in neurotrophin concentrations and decreased ADC in frontal lobes when compared with controls.